Effects of chemical oxidation on surface oxygen-containing functional groups and adsorption behavior of biochar. (September 2018) - Fan, Qinya; Sun, Jianxiong; Chu, Lei; Cui, Liqiang; Quan, Guixiang; Yan, Jinlong; Hussain, Qaiser; Iqbal, Muhammad
Abstract: Biochar is a beneficial soil amendment but the changes in its surface properties during the aging process, especially the oxygen-containing functional groups and the associated adsorption behaviors, are not well documented. In this paper, the aged wheat straw biochar was simulated by chemical oxidation with HNO3 -H2 SO4 and NaOH-H2 O2 systems. Characterization results showed that carbon loss and oxygen incorporation ran throughout the aging process. Surface oxygen-containing functional groups were found to be increased in all treated biochars, especially for carboxyl. Much more developed mesopores were observed in aging biochar, specific surface area was increased by 126% for biochar treated with NaOH-H2 O2, and 226% for biochar treated with 40% of HNO3 -H2 SO4 . Thermogravimetric analysis showed that the increasing oxygen-containing functional groups led to 14% and 30% mass loss by treating biochar with alkali and acid, respectively. The improved biochar surface through the increase of oxygen-containing functional groups enhanced the cadmium sorption capacity, and the sorption capacity increased by 21.2% in maximum. Roughed surface from oxidation was another reason for increasing cadmium adsorption. Results indicated that the adsorption performance of biochar on pollutant would be changed during aging process along with the changing surface properties. Graphical abstract: Image 1 Highlights: Carbon loss and oxygen incorporation ran throughout the oxidation. Aging layer formed on the biochar surface. Oxidant destroyed surface structure and developed much more mesopores. More oxygen-containing functional groups increased cadmium complexation. Long-term field remediated biochar showed much more carboxyl groups.